Upaya Meningkatkan Kemampuan Membaca Permulaan Anak Kelompok B1 melalui Metode Bercerita Gambar Berseri di TK ABA Brosot II Kulon Progo - Sulastri, Ambar; Haryanti, Haryanti (Piramida Akademi, 2024)
Beginning reading is a skill and cognitive process. The storytelling method is a learning strategy that can provide learning experiences to kindergarten students. A series of images is a series of images that form a story. The formulation of the problem in this research is how to improve the beginning reading skills of group B1 children through the serial picture storytelling method at the ABA Brosot II Kulon Progo Kindergarten? The aim is to find out how to improve the beginning reading skills of group B1 children through the serial picture storytelling method at the ABA Brosot II Kulon Progo Kindergarten. The type of research is Classroom Action Research (PTK). The instrument used was an observation sheet, the sample size was 13 children and the data was analyzed using a percentage formula. The results of the study showed an increase in children's initial reading abilities, from pre-cycle 35%, cycle I to 46%, and cycle II to 81%. Based on these data, it can be concluded that the serial picture storytelling method can improve the beginning reading skills of children in group B1 at ABA Brosot II Kindergarten, Kulon Progo.